Parents' Efforts to Improve Children's Learning Interests in Islamic Families in Indonesia - Putri, Indiani Hasana; Fitria, Yenni; Putri, Viona Yolanda; Firsya, Rahmatul Hasni; Jofanry, Rofif Octa; Putri, Fitria Desvi (International Journal of Islamic Studies Higher Education, 2022)
This study aims to analyze parents' efforts to increase children's interest in learning. This research uses qualitative methods with a case study approach. Data collection techniques used are interviews, observation, and documentation. Data sources were taken from six informants consisting of parents and elementary school children through direct interviews. All data were analyzed thematically using the Miles and Huberman technique. The results of the study as a whole describe nine main themes of parents' efforts to increase children's interest in learning, namely i) parents know children's learning development, ii) complete children's learning facilities, iii) guide children to study at home, iv) control children's study time, v) limiting the use of gadgets, vi) a comfortable learning environment, vii) children attend tutoring, viii) give rewards to children, xi) parents' economic influence